The role of filamin in gonadotropin releasing hormone receptor signalling and expression - Motlogelwa, Lawrence Katlego (My University, 2020)
Gonadotropin Releasing Hormone (GnRH) is the central regulator of reproductive development and function. When GnRH binds to its receptor it results in signal transduction cascades which eventually culminate in gonadotropin synthesis and secretion. These hormones in turn regulate steroidogenesis and gametogenesis. The GnRH receptor can activate various signalling pathways in pituitary gonadotropes, however the Gαq/11 protein kinase C (PKC) dependent extracellular signal-regulated (ERK) pathway remains the main pathway through which gonadotropin synthesis and secretion are mediated. The mechanisms underlying the GnRH receptor ERK pathway have not been fully defined, it is not clear how signal specificity of this pathway is maintained. One of the explanations is the presence of scaffolding proteins and signalling complexes (signalosomes), which have been shown to involve the cytoskeleton and associated proteins. Filamin A, an actin-binding cytoskeletal protein has been shown to modulate trafficking and signalling of several receptors. Filamin A organises complex cellular signals from the plasma membrane, cytoplasm to the nucleus. Filamin A has also been shown to interact with upstream effectors of ERK, namely PKC and mitogen activated protein kinase kinase (MEK 1). However, the role of filamin A in GnRH receptor signalling has not yet been studied. We investigated the role of filamin A in GnRH receptor signalling. Filamin A siRNAs were designed and synthesised to reduce filamin A protein expression in GnRH receptor-transfected HEK 293 cells, then GnRH receptor-mediated ERK phosphorylation was measured by western blotting. There was no significant difference in HEK 293 cells with normal and reduced protein expression of filamin A. GnRH receptor mediated ERK phosphorylation was also measured in GnRH receptor-transfected filamin A replete (M2A7) and deficient (M2) melanoma cells. GnRH receptor mediated ERK phosphorylation kinetics varied between M2A7 and M2 cells. ERK phosphorylation in the M2 cells reached its maximum after 15 minutes and started to decrease after 30 minutes. In contrast ERK phosphorylation in the M2A7 cells was elevated from 1 minute and sustained through to 60 minutes. Gonadotropin Releasing Hormone (GnRH) is the central regulator of reproductive development and function. When GnRH binds to its receptor it results in signal transduction cascades which eventually culminate in gonadotropin synthesis and secretion. These hormones in turn regulate steroidogenesis and gametogenesis. The GnRH receptor can activate various signalling pathways in pituitary gonadotropes, however the Gαq/11 protein kinase C (PKC) dependent extracellular signal-regulated (ERK) pathway remains the main pathway through which gonadotropin synthesis and secretion are mediated. The mechanisms underlying the GnRH receptor ERK pathway have not been fully defined, it is not clear how signal specificity of this pathway is maintained. One of the explanations is the presence of scaffolding proteins and signalling complexes (signalosomes), which have been shown to involve the cytoskeleton and associated proteins. Filamin A, an actin-binding cytoskeletal protein has been shown to modulate trafficking and signalling of several receptors. Filamin A organises complex cellular signals from the plasma membrane, cytoplasm to the nucleus. Filamin A has also been shown to interact with upstream effectors of ERK, namely PKC and mitogen activated protein kinase kinase (MEK 1). However, the role of filamin A in GnRH receptor signalling has not yet been studied. We investigated the role of filamin A in GnRH receptor signalling. Filamin A siRNAs were designed and synthesised to reduce filamin A protein expression in GnRH receptor-transfected HEK 293 cells, then GnRH receptor-mediated ERK phosphorylation was measured by western blotting. There was no significant difference in HEK 293 cells with normal and reduced protein expression of filamin A. GnRH receptor mediated ERK phosphorylation was also measured in GnRH receptor-transfected filamin A replete (M2A7) and deficient (M2) melanoma cells. GnRH receptor mediated ERK phosphorylation kinetics varied between M2A7 and M2 cells. ERK phosphorylation in the M2 cells reached its maximum after 15 minutes and started to decrease after 30 minutes. In contrast ERK phosphorylation in the M2A7 cells was elevated from 1 minute and sustained through to 60 minutes. Gonadotropin Releasing Hormone (GnRH) is the central regulator of reproductive development and function. When GnRH binds to its receptor it results in signal transduction cascades which eventually culminate in gonadotropin synthesis and secretion. These hormones in turn regulate steroidogenesis and gametogenesis. The GnRH receptor can activate various signalling pathways in pituitary gonadotropes, however the Gαq/11 protein kinase C (PKC) dependent extracellular signal-regulated (ERK) pathway remains the main pathway through which gonadotropin synthesis and secretion are mediated. The mechanisms underlying the GnRH receptor ERK pathway have not been fully defined, it is not clear how signal specificity of this pathway is maintained. One of the explanations is the presence of scaffolding proteins and signalling complexes (signalosomes), which have been shown to involve the cytoskeleton and associated proteins. Filamin A, an actin-binding cytoskeletal protein has been shown to modulate trafficking and signalling of several receptors. Filamin A organises complex cellular signals from the plasma membrane, cytoplasm to the nucleus. Filamin A has also been shown to interact with upstream effectors of ERK, namely PKC and mitogen activated protein kinase kinase (MEK 1). However, the role of filamin A in GnRH receptor signalling has not yet been studied. We investigated the role of filamin A in GnRH receptor signalling. Filamin A siRNAs were designed and synthesised to reduce filamin A protein expression in GnRH receptor-transfected HEK 293 cells, then GnRH receptor-mediated ERK phosphorylation was measured by western blotting. There was no significant difference in HEK 293 cells with normal and reduced protein expression of filamin A. GnRH receptor mediated ERK phosphorylation was also measured in GnRH receptor-transfected filamin A replete (M2A7) and deficient (M2) melanoma cells. GnRH receptor mediated ERK phosphorylation kinetics varied between M2A7 and M2 cells. ERK phosphorylation in the M2 cells reached its maximum after 15 minutes and started to decrease after 30 minutes. In contrast ERK phosphorylation in the M2A7 cells was elevated from 1 minute and sustained through to 60 minutes. Furthermore, ligand affinity and cell surface receptor expression were assessed using competition binding assays, effector coupling was assessed by measuring GnRH receptor-mediated IP production using IP assays. Filamin A is not required for GnRH receptor-mediated ERK phosphorylation, but its presence results in rapid and sustained GnRH receptor-mediated ERK phosphorylation. Furthermore, the latter is not due to changes in GnRH ligand binding affinity, cell surface receptor expression or G protein coupling. These results suggest that filamin A is part of the GnRH receptor signalosome and is required for enhanced ERK phosphorylation, thus filamin A may have a role in the regulation of reproductive development and function.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020